Single metal deposition versus physical developer: A comparison between two advanced fingermark detection techniques. (January 2019) - Moret, Sébastien; Lee, Po Lun Timothy; de la Hunty, Mackenzie; Spindler, Xanthe; Lennard, Chris; Roux, Claude
Highlights: SMD II was compared to PD as standalone and after amino acid reagents on more than 1000 fingermarks. The performance of SMD II was judged to be inferior to that of PD. SMD II is less affected by donor variability and can be applied on both porous and non-porous substrates. PD is less affected by substrate variability and wetting of the substrate. Abstract: Single metal deposition (SMD II) is a fingermark detection technique based on the use of colloidal gold. The technique has been simplified and optimised over the years to become more reliable, sensitive and user-friendly. Physical developer (PD) is a well-established detection method based on silver deposition from a redox solution. This study presents an extensive comparison of SMD II against PD for fingermark detection on porous substrates. The two techniques were compared as (i) standalone methods, (ii) in sequence after the application of routine amino acids reagents (1, 2-indanedione/zinc followed by ninhydrin), and (iii) after the substrates have been wet. More than 1000 fingermark specimens were processed. Overall, the performance of SMD II was judged to be inferior to that of PD; therefore, SMD II cannot be recommended as a valid replacement for fingermark detection on porous substrates. Indanedione/zinc and ninhydrin application negatively impacts on SMD II performance and the technique gave inconsistent results across the selected range of porous substrates. Moreover, the detected fingermarks lacked contrast making their visualisation difficult. However, even if PD remains the technique of choice, SMD II showed significant potential. It proved to be less affected by donor variability and it can be applied on both porous and non-porous substrates. It did not lead to uncontrolled background staining that commonly occurs with PD. If contrast and consistency issues can be addressed in future research, SMD II may become a viable alternative to PD.